Relationship of Family Support with Vegetable and Fruit Consumption Behavior - Untung Halajur (Institute of Medico-legal Publications Pvt Ltd, 2020)
The family approach is the development of a home visit by the public health center effort. one of the activities is community management support system in supporting a culture of healthy living in the family. Family support is needed to behave in the consumption of vegetables and fruit every day. Clean and healthy living behavior in the household or family structure is one of the goals in clean and healthy behavior. There are 10 indicators of clean and healthy behavior in family settings, one of them is the consumption of vegetables and fruit every day. This study aims to analyze the relationship between family support and the consumption of vegetables and fruits in children. The research design used in this study is research cross sectional. The research sample is Golden Christian School elementary school students. The time of the study was in May and June 2018. The results showed that there was no significant relationship between emotional and assessment support for vegetable and fruit consumption behavior in children. There is a significant relationship between instrumental support and information support with vegetable and fruit consumption behaviors in children, respectively p-value 0.015 and 0.041. It is recommended that the school provide knowledge to parents whose children are vulnerable not to consume vegetables and fruits in order to support the healthy indonesia program with a family approach.